What is the Matter with Mary Jane? - Harmer, Wendy (Teenage., 2014)
IN THE MIRRORWhen I am skinny ... I'll laugh all the timeI'll be very coolI'll be in the magazinesAnd look good at the poolThe sun will be shiningI'll drive a fast carI'll meet Justin TimberlakeI'll be a star. AT THE TABLE[To Mum] What's this? Eggplant?[To audience] What's she got eggplant on here for? [To audience] How many calories has eggplant got? I think it's got 36. HOSPITALUh Oh ... I've really done it this time. I'm in hospital. The embarrassing thing is ... there's nothing wrong with me. Well, nothing that a sausage roll wouldn't fix. If I could eat a sausage roll. If I could eat anything. But.